Risk-adjusted performance of Malaysian Real Estate Investment Trust Funds - Low, Soo Wah; Anwar Johari (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study evaluates performance and risk features of Malaysian REIT funds from 2007-2012. Performance evaluation methods employed are Sharpe, Treynor, Jensen, and M-squared measures. The results indicate that beta values are all less than one and that the total risk of REIT funds comes mostly from the unsystematic risk component. While the results emphasize the importance of embedding risk into performance analyses, the findings also provide caution that differences in the risk measures employed give rise to contradictory performance rankings. The low R-squared values for REIT funds suggest low reliability of beta coefficients. The findings therefore imply that the Sharpe ratio and the M-squared measure which quantify risk using standard deviation of return provide more convincing and meaningful performance evaluation than the Treynor and Jensen measures. The results of M-squared measure also illustrate how leverage can be applied as a tool in achieving optimal REIT performance. The findings provide good insights to managers in assessing REIT performance and to investors who are considering REIT as a potential investment vehicle.